Mitigating Risks in the Disaster Management Cycle - Huay Ling Tay; Ruth Banomyong; Paitoon Varadejsatitwong; Puthipong Julagasigorn (Advances in Civil Engineering)
Purpose. The disaster management cycle (DMC) is often considered part of the essential efforts to handle disaster risk and consists of four key phases, namely preparedness, response, recovery, and mitigation. The purpose of this conceptual article is two-fold. The first is to identify dominant risks, and the second is to propose risk mitigation strategies for these four phases in the DMC. Design/Methodology/Approach. The study uses primary and secondary data to identify the dominant risks in each DMC phase. The primary data sources include responses from an online questionnaire and transcripts from three semi-structured interviews with stakeholders in the humanitarian supply chain. The secondary data sources include practitioner reports and archival data triangulation. Findings. The findings reveal five dominant risk factors in the DMC and classify them within the DMC phases, which are (1) demand risk, (2) supply risk, (3) operational risk, (4) infrastructure risk, and (5) disruption risk. The severity and frequency of each risk vary in each DMC phase. We found that several supply chain strategies (SCSs), such as raising risk awareness and horizontal and vertical collaboration and coordination among the key stakeholders in the DMC, can be essential risk mitigation strategies that apply across the four DMC phases. Research Limitations/Implications. The study highlighted dominant risks and the appropriate SCSs for mitigating the risk factors within each DMC phase. These findings are encapsulated in a conceptual framework for guiding risk prioritisation, decision-making, and policy-making. Our study has several limitations. First, although we followed a systematic process in computing the risk scores based on the likelihood of occurrences and impacts, the scores are nonetheless considered subjective perceptions of the respondents. Second, the number of respondents was limited. Broader coverage of respondents across geographical regions will provide further insights into the perspectives on the relevant risk factors in the DMC phases. This leaves possibilities for future research, comparison with other risk computation methods, and evaluation. Originality/Value. This study is one of the few that collected multiple data to extend the knowledge of risk identification and mitigation within the DMC.